Relational Sociological and Intersectional Research About Pain: The Case of Turkey - Kasapoglu, Aytul; Yel, Cigdem (Advances in Social Sciences Research Journal, 2022)
Until recent years, there has been an alternative search for pain, which has been studied in accordance with the Specificity Theory and the Bio-medical Model. Among these, the bio-psychosocial model and the relational and intersectionality approaches compatible with it come first. The Primary aim of this study is to apply alternative models to the deficiencies of the bio-medical model and to show their contributions. For this purpose, physical, psychological, cognitive and social factors, which Gate Control Theory accepts as components of pain, were comparatively examined based on the life stories of seven participants, four of whom were women, with an average age of 75 years. In the light of the principles of relational and intersectional approaches that reject essentialism, focus on uncertainties, and try to reveal difference and diversity, the findings are discussed with the relevant current literature. Research findings show that as the participants get older, their physical problems increase and they experience health problems. While some of the participants, who are generally alone after the loss of their spouses, live alone, some of them stay with their children. Since Anatolian traditional culture does not encourage institutional care much, the disadvantages of living with children, such as loss of power in subordinate or weaker social status, as well as the advantages of living with children, carry them to liminal status. It has been observed that the women in the research are more successful in managing their emotions and reframing the pain they have suffered better than the men, with the resignation stemming from the traditional culture as well as the struggles they have fought throughout their long lives. As a result, it has been tried to contribute to science by showing the advantages of the holistic view of alternative models, as well as the deficiencies of the bio-medical model, which is the basis of classical Western medicine, through examples from outside the West.